Chemoenzymatic Route for the Synthesis of (S)‐Moprolol, a Potential β‐Blocker. Issue 4 (28th January 2016) - Ghosh, Saptarshi; Bhaumik, Jayeeta; Banoth, Linga; Banesh, Sooram; Banerjee, Uttam Chand
Abstract: A biocatalytic route for the synthesis of a potential β‐blocker, (S)‐moprolol is reported here. Enantiopure synthesis of moprolol is mainly dependent on the chiralintermediate, 3‐(2‐methoxyphenoxy)‐propane‐1, 2‐diol. Various commercial lipases were screened for theenantioselective resolution of (RS)‐3‐(2‐methoxyphenoxy)propane‐1, 2‐diol to produce the desired enantiomer. Among them, Aspergillus niger lipase (ANL) was selected on the basis of both stereo‐ and regioselectivity. The optimized values of various reaction parameters were determined such as enzyme (15 mg/mL), substrate concentration (10 mM), organic solvent (toluene), reaction temperature (30 °C), and time (18 h).The optimized conditions led to achieving >49% yield with high enantiomeric excess of (S)‐3‐(2‐methoxyphenoxy)propane‐1, 2‐diol. The lipase‐mediatedcatalysis showedregioselective acylation with dual stereoselectivity. Further, the enantiopureintermediate was used for the synthesis of (S)‐moprolol, which afforded the desired β‐blocker. Chirality 28:313–318, 2016 . © 2016 Wiley Periodicals, Inc. Abstract : A biocatalytic route for the synthesis of a potential β‐blocker, ( S )‐moprolol is reported here. Lipase mediated kinetic resolution methodology was used for the enantiopure synthesis of the chiral diol‐intermediate, as a green and cost‐effective approach. The lipase mediated catalysis showed regioselective acylation with dual stereoselectivity. Further, the enantiopure intermediate was used for the synthesis of ( S )‐moprolol, which afforded the desired β‐blocker. The enzymatic switch towards the synthesis of ( S )‐moprolol sets an excellent example of green synthesis